An experimental coin-sized radio for extremely low-power WPAN (IEEE 802.15.4) application at 2.4 GHz. - Pilsoon Choi (IEEE Journal of solid state circuits)
An experimental 2.4-GHz CMOS radio composed of RF and digital circuits for the low-power and low-rate preliminary IEEE802.15.4 WPAN is reported, consuming 21 mW in receive mode and 30 mW in transmit mode. The RF design focus is to maximize linearity for a given power consumption using linearization methods which lead an order of magnitude improvement in LNA/mixer IIP3/power performance. Chip-on-PCB technology allows implementation of a coin-sized radio at very low cost, which also provides 3 dBi gain patch antenna and high Q (>50) inductors.